2020
DOI: 10.2118/200485-pa
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Production Interference Level Due to Fracture Hits Using Diagnostic Charts

Abstract: Summary The objective of this study is to develop a new method that leads to diagnostic charts that quantify the pressure response between two interfering wells. Analytical linear flow models for single hydraulic fracture are used to develop a fracture hit model, which is next verified with a numerical model for validity. An analytical two-fracture model is then developed to simulate flowing bottomhole pressure (BHP) of a shut-in well, which interferes with the other well through a fracture hit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The interaction of hydraulic and natural fractures makes forecasting the performance of wells in such reservoirs a major challenge [12,13]. Alternatively, conductive natural fractures may promote pressure communication between the adjoining hydraulic fractures and wells, which increase the well/fracture interference [14]. The nonconductive natural fractures may affect the sweep pattern due to waterflood between the injector and the producer wells [15].…”
Section: Applicationmentioning
confidence: 99%
“…The interaction of hydraulic and natural fractures makes forecasting the performance of wells in such reservoirs a major challenge [12,13]. Alternatively, conductive natural fractures may promote pressure communication between the adjoining hydraulic fractures and wells, which increase the well/fracture interference [14]. The nonconductive natural fractures may affect the sweep pattern due to waterflood between the injector and the producer wells [15].…”
Section: Applicationmentioning
confidence: 99%
“…In addition to the pressure-decline effect, hydraulic fractures of adjacent wells may connect during the fracture-treatment operation [19]. If permanent pressure communication is established, the two wells effectively represent an integrated production system [20], which predicts the well behavior more challenging [2,4].…”
Section: Fracture-spacing Effects With Flow-cell Modelmentioning
confidence: 99%
“…Fiallos et al investigate the well interference in the Eagle Ford shale reservoir using numerical models in the combination of an embedded discrete fracture model (Fiallos et al 2019). Yang et al developed a two-fracture model to simulate the bottom-hole pressure (BHP) response of the two-well system with frac hits among simple fractures during shut-in period (Yang et al 2020). He et al researched the mechanism and dominated factors behind interwell fracturing interference in multi-well pads and found that a minor pressure difference between the infill well and parent wells is preferred to prevent fracturing interference (He et al 2020).…”
Section: Introductionmentioning
confidence: 99%